Culinary Resistance? - O'Neill, Brian Juan (Trabalhos de Antropologia e Etnologia, 2020)
Can James C. Scott’s model of resistance be extended to the field of cuisine? To what extent can a group resist through food and cooking? This paper poses these two queries within the context of a Malaysian foodscape: the Kristangs, or Portuguese Eurasians, of polyethnic Malacca. A series of cultural “worlds” has architectured this multicultural Creole group and includes Indian, Chinese, and Malay worlds in action prior to the arrival of Portuguese colonos in 1511, as well as the later Dutch and British colonial regimes. By simply persisting, or enduring, the group is also resisting; cuisine comprises a key element in this persistence. By sidestepping the dominant/dominated lens, we can focus more clearly on the group’s positive strategies of resistance through cooking. One major implication for Action Theory is that they have practiced the Art of Resisting via the Art of Persisting.